The Size Effect in Value and Momentum Factors: Implications for the Cross-section of International Stock Returns - Victoria Atanasov; Thomas Nitschka (Tinbergen Institute, 2013)
We document a consistent and robust relation between expected equity premia and common risk factors constructed on the basis of small stocks. Empirically, we show that (i) small-stock components of traditional value and momentum factors capture patterns in returns on regional and global portfolios of stocks; (ii) size-effect models substantially outperform benchmark models in finance; (iii) global small-stock value and momentum components are priced but regional models lead to more accurate asset evaluations; (iv) funding liquidity risk is a partial explanation of these findings.
Keywords: G11; G12; 330; international stock returns; size; value; momentum